Arginine vasopressin hormone receptor antagonists in experimental autoimmune encephalomyelitis rodent models: A new approach for human multiple sclerosis treatment - Calvillo-Robledo, Argelia; Ramírez-Farías, Cynthia; Valdez-Urias, Fernando; Huerta-Carreón, Erika P.; Quintanar-Stephano, Andrés (Frontiers in Neuroscience, 2023)
Multiple sclerosis (MS) is a chronic demyelinating and neurodegenerative disease that affects the central nervous system. MS is a heterogeneous disorder of multiple factors that are mainly associated with the immune system including the breakdown of the blood-brain and spinal cord barriers induced by T cells, B cells, antigen presenting cells, and immune components such as chemokines and pro-inflammatory cytokines. The incidence of MS has been increasing worldwide recently, and most therapies related to its treatment are associated with the development of several secondary effects, such as headaches, hepatotoxicity, leukopenia, and some types of cancer; therefore, the search for an effective treatment is ongoing. The use of animal models of MS continues to be an important option for extrapolating new treatments. Experimental autoimmune encephalomyelitis (EAE) replicates the several pathophysiological features of MS development and clinical signs, to obtain a potential treatment for MS in humans and improve the disease prognosis. Currently, the exploration of neuro-immune-endocrine interactions represents a highlight of interest in the treatment of immune disorders. The arginine vasopressin hormone (AVP) is involved in the increase in blood−brain barrier permeability, inducing the development and aggressiveness of the disease in the EAE model, whereas its deficiency improves the clinical signs of the disease. Therefore, this present review discussed on the use of conivaptan a blocker of AVP receptors type 1a and type 2 (V1a and V2 AVP) in the modulation of immune response without completely depleting its activity, minimizing the adverse effects associated with the conventional therapies becoming a potential therapeutic target in the treatment of patients with multiple sclerosis.